VARIABEL ASESTABILITAS INVESTASI PADA PRODUK PERBANKAN/TABUNGAN BERJANGKA (Studi Kasus Pada PT. Bank Tabungan Pensiunan Nasional – BTPN Cabang Jember) - Wita Vianika; Karim Budiono (RELASI : JURNAL EKONOMI, 2013)
There are seventeen commercial banks that operate at Jember, they have similar services products but the  different between them is the interest rate and their to the costomers, so that competation among banks to be highly competitive. This research at PT. Bank Tabungan Pensiunan Nasional (BTPN), Tbk than have specific market segments as compared to other banks. The independent variables in this research are interest rate (X1), promotion (X2), product (X3), eference group (X4) and location (X5) and the dependent variable is number of clients who invest  at limited deposits.  The purpose of this research are to know which of independent variables that influce the dependent variable and to know which of independent variables most dominant to dependent variable and interest rate is the most dominant variable in this research.  Finally, the conclution that we can suggest are the main priority about policy interest rate and the other variables most improve their performance because they have positive correlation.